2022
DOI: 10.1007/s11157-022-09622-3
|View full text |Cite
|
Sign up to set email alerts
|

A review of the emergence of antibiotic resistance in bioaerosols and its monitoring methods

Abstract: Despite significant public health concerns regarding infectious diseases in air environments, potentially harmful microbiological indicators, such as antibiotic resistance genes (ARGs) in bioaerosols, have not received significant attention. Traditionally, bioaerosol studies have focused on the characterization of microbial communities; however, a more serious problem has recently arisen due to the presence of ARGs in bioaerosols, leading to an increased prevalence of horizontal gene transfer (HGT). This const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 135 publications
(263 reference statements)
0
18
0
1
Order By: Relevance
“…(Horiuk et al, 2018;Morgado-Gamero et al, 2021). Поширення збудників захворювання у клініках можливе через біоаерозольсукупність мертвих та живих мікроорганізмів, шерсті, клітин епітелію, завислих в повітрі тощо (Tsay et al, 2020;Lee & Yoo, 2022). Отже, у боксах з перетримування хворих тварин за неефективної дезінфекції або інтенсивного використання приміщень створюються сприятливі умови для формування стійкої мікрофлори.…”
Section: вступunclassified
“…(Horiuk et al, 2018;Morgado-Gamero et al, 2021). Поширення збудників захворювання у клініках можливе через біоаерозольсукупність мертвих та живих мікроорганізмів, шерсті, клітин епітелію, завислих в повітрі тощо (Tsay et al, 2020;Lee & Yoo, 2022). Отже, у боксах з перетримування хворих тварин за неефективної дезінфекції або інтенсивного використання приміщень створюються сприятливі умови для формування стійкої мікрофлори.…”
Section: вступunclassified
“…The study of the carriage of ESBL-producing Enterobacterales in WWTP workers and surrounding residents shows that these groups are much more like to acquire bacteria harboring the ESBL mechanism [ 25 ], thus confirming the direct influence of WWTPs on spreading ARGs into air. The contribution of WWTPs’ bioaerosols in ARGs and ARB propagation into air and different environments is commonly investigated [ 143 , 144 , 145 , 146 ]. For example, Gaviria-Figueroa et al studied bioaerosol samples collected downwind from sludge aeration tanks and showed a significant presence of clinically relevant class A β-lactamases, along with other classes of these enzymes and different antibiotic groups [ 147 ].…”
Section: Clinically Significant β-Lactam Resistance Genes In Wastewat...mentioning
confidence: 99%
“…They were found to play a vital role in the pathogen transmission of respiratory diseases (20)(21)(22)(23). According to the different main components of microbial aerosols, they can be divided into bacterial aerosols, fungal aerosols, and virus aerosols (24), of which bacterial and fungal aerosols account for a relatively large proportion (25). For many years, the monitoring of microbial aerosol concentrations and distributions in indoors environment and atmospheric environment has always been an important topic for scholars.…”
Section: Types and Distribution Of Microbial Aerosolsmentioning
confidence: 99%